Social Enterprise Model in Waqf Land Management in Bantul, Indonesia - Unggul Priyadi; Siti Achiria (Program Studi Ilmu Agama Islam Program Magister, Universitas Islam Indonesia, 2022)
Bantul Regency have 92.05 hectare waqf land, spread over 2,959 locations. So far, 76 per cent of waqf land is used for mosques/musholla. At the same time, waqf land assets can be empowered to alleviate poverty. This study aims to: 1) optimise the utilization of waqf land assets through simulation of hydroponic cultivation and biofloc; 2) find a poverty alleviation model through the development of waqf land assets; 3) describe the implications of the implementation of the model. The method used in this research is descriptive qualitative, carried out by simulation and interviews with the community. Kapanewon Sedayu and Kapanewon Banguntapan are the main focus of the study and implementation of waqf land assets, considering that Bantul Regency had the highest number of poor people in 2020, as many as 138.066 people. The results show that based on the simulation, waqf land assets allow for community empowerment and the formulation of a waqf land asset management model through the Model of Islamic Social Entrepreneurship, and there are several implications for empowering the poor.